Case Report: Right atrial mass arising from the Eustachian valve - Jolou, Jalal; Martineau, Jérôme; Müller, Hajo; Cikirikcioglu, Mustafa; Huber, Christoph (Frontiers in Cardiovascular Medicine, 2023)
A mass in the right atrium (RA) is an unusual finding that warrants further investigation. We report the case of a 72-year-old male patient who underwent a Bentall operation with a biological composite graft and closure of patent foramen ovale 18 months prior to his presentation with an incidental new RA mass during follow-up echocardiography. Transesophageal echocardiography and thoracic CT angiography confirmed a right atrial mass attached to the Eustachian valve and additionally revealed a non-occlusive pulmonary embolism in the inferior lobar artery of the left lung. Despite 2 months of anticoagulation treatment, the size of the mass did not decrease. Further MRI imaging showed a central mass enhancement which raised concerns about a tumoral lesion. Following a discussion with the local Heart Team, management with surgical treatment was decided. The intraoperative findings revealed a 2.5 cm × 2.1 cm mass arising from the Eustachian valve and a non-diagnosed Chiari network in the RA. Both were resected and sent for a frozen section procedure which excluded a malignancy. The final histopathological analysis described fibrotic tissues compatible with an organized thrombus. The patient was discharged on postoperative day 7 without any complications. Although imaging studies are useful for the initial and differential diagnosis of RA masses, it is not always possible to get the final diagnosis without surgery. In case of a suspicion of a potentially malignant pathology, surgical exploration and resection are necessary.